PERANCANGAN SISTEM CHARGING BATERAI DENGAN DC-DC CONVERTER BERBASIS PANEL SURYA - Supriadi jumandi; Irsan Adiansyah; I Made Andik Setiawan; Surojo Surojo (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
This study aims to create a solar panel-based battery charging system with a buck boost converter as a control component. The method used is a quantitative method, namely by means of experiments and data collection on each component. The solar panel component used is 100 Wp and can produce a maximum voltage of 12,6 volts. The voltage from solar panels is used as a source of battery charging. The battery used is a 12V 7Ah. In the battery charging process, a buck boobt converter is used as a voltage controller that can increase or decrease the voltage from an unstable solar panel. The voltage used in the battery charging process, the faster the battery will charge. The time required to charge the battery from a voltage of 11,49 volts to 12,48 volts is 80 minutes.